Impacts of tuberculosis services strengthening and the COVID-19 pandemic on case detection and treatment outcomes in Mimika District, Papua, Indonesia: 2014-2021. - Trisasi Lestari; Kamaludin; Christopher Lowbridge; Enny Kenangalem; Jeanne Rini Poespoprodjo; Stephen M Graham; Anna P Ralph (Public Library of Science (PLoS), 2022)
Indonesia is a high-burden tuberculosis (TB) country with a wide case detection gap, exacerbated by the COVID-19 pandemic. We aimed to review the epidemiology of TB in a high-endemic setting of Indonesia before and during the implementation of health system strengthening activities for TB, including during the first two years of the COVID-19 pandemic. We analysed TB program data from Mimika District, Papua, Indonesia from 2014 to 2021. Health system strengthening activities to improve the programmatic management of TB were implemented from 2017 onwards. Activities included decentralization of TB services, training and mentoring of healthcare workers, improved screening for co-morbidities, and introduction and optimisation of Xpert testing in 2018. A total of 11,803 TB cases were notified to the Mimika District Health Office over eight years (2014-21). Between 2015 and 2019, there was a 67% increase in annual case notifications, an 89% increase in bacteriologically confirmed cases and the proportion of TB cases detected in primary care increased from 26% to 46%. In 2020, coinciding with the COVID-19 pandemic, investigation of people with presumptive TB fell by 38%, but the proportion of those tested with Xpert increased. TB case notifications decreased by 19% from 1,796 in 2019 to 1,461 in 2020, but then increased by 17% to 1,716 in 2021. Routine screening for co-morbidities (HIV, diabetes) among TB patients improved over time and was not affected by the pandemic. Treatment success overall was 71% and remained relatively unchanged. Loss to follow-up and death were 18% and 3.7% respectively. Improvements in TB case finding were observed over a period in which a range of health system strengthening activities were implemented. While COVID-19 had a negative impact on the TB program in Mimika District, there are encouraging signs of recovery. Further work is needed to improve TB treatment outcomes.